The Contribution of an Infectious Workup in Understanding Stillbirth - Fouks, Yuval; Many, Ariel; Shulman, Yael; Bak, Stella; Shinar, Shiri (American Journal of Perinatology, 2019)
Objective This study was aimed to assess the utility of diagnostic tests of maternal and fetal infection in the evaluation of stillbirth.Study Design A single-center retrospective study from January 2011 to December 2016 of all women presenting to the hospital with intrauterine fetal death at or after 20 weeks of gestation. Standard evaluation included review of medical records, clinical and laboratory inflammatory workup, maternal serologies, fetal autopsy, placental pathology, and fetal and placental cultures. A suspected infectious etiology was defined as meeting at least two diagnostic criteria, and only after exclusion of any other identifiable stillbirth cause.Results During the 7-year study period, 228 cases of stillbirth were diagnosed at our center. An infectious etiology was the suspected cause of stillbirth in 35 cases (15.3%). The mean gestational age of infection-related stillbirth was 28 1/7 (range: 22–37) weeks, while for a noninfectious etiology, it was 34 0/7 (range: 25–38) weeks (p = 0.005). Placental histological findings diagnostic of overt chorioamnionitis and funisitis were observed in 31 (88.5%) cases. In 16 (45.7%) cases the placental and fetal cultures were positive for the same pathogen. Serology of acute infection was positive in three (8.5%) of the cases.Conclusion Maternal and fetal infectious workup is valuable in the investigation of stillbirth, particularly before 30 weeks of gestation and should be considered a part of standard evaluation.
Keywords: stillbirth; infection; infectious; workup; chorioamnionitis